Predicting Muslim Female Customer Retention Through Islamic Marketplace Attractiveness - Riofita, Hendra (Universitas Muhammadiyah Yogyakarta, 2024)
This study aims to employ Islamic marketplace attractiveness to predict Muslim female customer retention and price attributes to trigger the predictor effect to encourage Islamic marketplaces to lead Indonesian e-commerce. The data were processed with SPSS and Amos programs and collected through the questionnaire filled in by 407 respondents taken using purposive, snowball, and non-probable sampling methods in a survey conducted for 2 months. The respondents were Muslim female customers who had experience purchasing fashion products in Islamic marketplaces. The Findings show that Islamic marketplace attractiveness is the predictor of Muslim female customer retention. Meanwhile, price attributes partially trigger the Islamic marketplace attractiveness effect on Muslim female customer retention. The findings are insights from Indonesia for developing countries, especially for Muslim developing countries, to encourage Islamic marketplaces to lead e-commerce, especially for their digital economic growth, by predicting Muslim female customer retention. All research constructs can implement the Theory of Reasoned Action in an e-commerce context. Since the theory reveals that behavior is determined by a predictor, Islamic marketplace attractiveness is the predictor of Muslim female customer retention on Islamic marketplaces. Meanwhile, price attributes are the trigger for the predictor effect on Muslim female customer retention.